Labour Supply and Commuting - Eva Gutiérrez-i-Puigarnau; Jos van Ommeren (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
We examine the effect of commuting on labour supply patterns. A labour supply model is introduced which shows that commuting distance increases daily workhours, whereas the effect on total labour supply is ambiguous. This paper addresses these issues empirically using the socio-economic panel data for Germany between 1997 and 2007. Endogeneity of commuting distance is accounted for by using employer-induced changes in commuting distance. In line with the theoretical model developed, we find that commuting distance has a slight positive effect on daily workhours. Further, we find a similar effect on weekly labour supply, but no effect on workdays. Distinguishing between males and females, it appears that the effects on labour supply are mainly through the behaviour of females, but the effects for females are still small.
Keywords: J22; R41; 330; Commuting; congestion tax; labour supply